2020
DOI: 10.2147/ott.s283574
|View full text |Cite
|
Sign up to set email alerts
|

VUp-Regulation of VCAN Promotes the Proliferation, Invasion and Migration and Serves as a Biomarker in Gastric Cancer [Corrigendum]

Abstract: OncoTargets and Therapy is an international, peer-reviewed, open access journal focusing on the pathological basis of all cancers, potential targets for therapy and treatment protocols employed to improve the management of cancer patients. The journal also focuses on the impact of management programs and new therapeutic agents and protocols on patient perspectives such as quality of life, adherence and satisfaction. The manuscript management system is completely online and includes a very quick and fair peer-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Studies have demonstrated that VCAN is upregulated in several tumors such as renal carcinoma, gastric cancer, pancreatic cancer, and colon cancer [33][34][35][36][37], and is expressed predominantly in cancer stroma rather than in epithelial components [36,37]. Our study found that VCAN was highly expressed in 96.88% of MTSCCs, which is consistent with previous findings [34,36]. The role of SOSTDC1 as a bone morphogenetic protein antagonist [38] in malignant tumors has not been fully clarified.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Studies have demonstrated that VCAN is upregulated in several tumors such as renal carcinoma, gastric cancer, pancreatic cancer, and colon cancer [33][34][35][36][37], and is expressed predominantly in cancer stroma rather than in epithelial components [36,37]. Our study found that VCAN was highly expressed in 96.88% of MTSCCs, which is consistent with previous findings [34,36]. The role of SOSTDC1 as a bone morphogenetic protein antagonist [38] in malignant tumors has not been fully clarified.…”
Section: Discussionsupporting
confidence: 84%
“…VCAN is one of the main components of the ECM, and plays an essential role in cell adhesion, proliferation, migration, and angiogenesis [31,32]. Studies have demonstrated that VCAN is upregulated in several tumors such as renal carcinoma, gastric cancer, pancreatic cancer, and colon cancer [33][34][35][36][37], and is expressed predominantly in cancer stroma rather than in epithelial components [36,37]. Our study found that VCAN was highly expressed in 96.88% of MTSCCs, which is consistent with previous findings [34,36].…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer (GC) is one of the most common malignant tumors in the world, with a poor prognosis and a severe threat to human health [ 1 ]. The primary method of diagnosis for GC is endoscopy and biopsy, which are invasive and expensive and can cause discomfort and anxiety to patients [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The primary method of diagnosis for GC is endoscopy and biopsy, which are invasive and expensive and can cause discomfort and anxiety to patients [ 2 ]. Radical gastrectomy remains the major method for the treatment of GC, but the diagnostic rate of early GC is less than 10%, which is mainly confirmed in the late stage of metastatic GC [ 1 , 3 , 4 ]. Accordingly, understanding the pathogenesis and identifying reliable prognostic biomarkers are urgent for effective treatment, which helps to improve the quality of life and survival of GC patients.…”
Section: Introductionmentioning
confidence: 99%
“…RGS2 is a multifunctional RGS protein that effectively interferes with signal transduction by coupling with Gqa receptors, thereby regulating multiple G protein-linked signaling pathways (53). VCAN is a chondroitin sulfate proteoglycan that affects cell adhesion, proliferation, migration and angiogenesis, and also participates in multiple pathological processes such as nervous system and circulatory system (54). CPVL may promote human tumor progression by inhibiting STAT1 pathway through interacting with BTK/p300 axis (55).…”
Section: Discussionmentioning
confidence: 99%